Observation of a new excited D+s meson in B0→D−D+K+π− decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2021)
Using pp collision data corresponding to an integrated luminosity of 5.4 fb−1 collected with the LHCb detector at a center-of-mass energy of 13 TeV, the B0→D−D+K+π− decay is studied. A new excited D+s meson is observed decaying into the D+K+π− final state with large statistical significance. The pole mass and width, and the spin parity of the new state are measured with an amplitude analysis to be mR=2591±6±7 MeV, ΓR=89±16±12 MeV, and JP=0−, where the first uncertainty is statistical and the second systematic. Fit fractions for all components in the amplitude analysis are also reported. The new resonance, denoted as Ds0(2590)+, is a strong candidate to be the Ds(21S0)+ state, the radial excitation of the pseudoscalar ground-state D+s meson.
Im Titel sind"+", "-" und "0" hochgestellt und "s" ist tiefgestellt
Gesehen am 21.06.2021